Regulations of miR-183-5p and Snail-Mediated Shikonin-Reduced Epithelial-Mesenchymal Transition in Cervical Cancer Cells - Tang Q; Liu L; Zhang H; Xiao J; Hann SS (Dove Medical Press, 2020)
Qing Tang,1,* Lihua Liu,2,* Hongyan Zhang,2,* Jing Xiao,2 Swei Sunny Hann1,3 1Laboratory of Tumor Biology, The Second Clinical College of Guangzhou University of Chinese Medicine, Guangzhou, Guangdong Province 510120, People’s Republic of China; 2Department of Gynecology, The Second Clinical College of Guangzhou University of Chinese Medicine, Guangzhou, Guangdong Province 510120, People’s Republic of China; 3Guangdong Provincial Key Laboratory of Clinical Research on Traditional Chinese Medicine Syndrome, The Second Clinical College of Guangzhou University of Chinese Medicine, Guangzhou, Guangdong Province 510120, People’s Republic of China*These authors contributed equally to this workCorrespondence: Swei Sunny Hann; Jing Xiao No. 111, Dade Road, Guangzhou, Guangdong Province 510120, People’s Republic of ChinaTel +86 20-39318472Email hann2012@outlook.com; xiaojingson_2004@126.comBackground: Shikonin, the main ingredient of Lithospermum erythrorhizon, has been reported to have antitumor effects via multiple targets and signaling pathways. However, the detailed mechanism underlying the effects in cervical cancer still remained unknown.Methods: MTT, wound-healing, transwell assays and flow cytometry experiments were used to measure cell growth, migration, invasion, and cell cycle analysis. Western blot was used to examine protein levels of Snail, Vimentin and E-cadherin. The expression level of miR-183-5p was measured via qRT-PCR. The E-cadherin promoter activity was detected via Secrete-PairTM Dual Luminescence Assay Kit. The transient transfection experiments were used for silencing of E-cadherin and overexpression of Snail genes. Tumor xenograft and bioluminescent imaging experiments were carried out to confirm the in vitro findings.Results: We showed that shikonin inhibited cell viability, migration and invasion, and induced cell cycle arrest in a dose-dependent manner in cervical cancer Hela and C33a cells. Mechanistically, we found that shikonin increased miR-183-5p expression and inhibited expression of transcription factor Snail protein. The mimics of miR-183-5p reduced, while the inhibitors of miR-183-5p reversed shikonin-inhibited Snail protein expression. In addition, shikonin decreased Vimentin, increased E-cadherin protein expressions and E-cadherin promoter activity, the latter was reversed in cells transfected with exogenous Snail overexpression vectors. Moreover, silencing of E-cadherin significantly abolished shikonin-inhibited cervical cancer cell growth. Similar findings were also observed in vivo using one xenograft mouse model.Conclusion: Our results show that shikonin inhibits EMT through inhibition of Snail and stimulation of miR-183-5p expressions, which resulted in induction of E-cadherin expression. Thus, blockade of EMT could be a novel mechanism underlying the anti-cervical cancer effects of shikonin.Keywords: shikonin, EMT, cervical cancer, miR-183-5p, Snail, E-cadherin